If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + u)(2u + 3) = 0 Reorder the terms: (1 + u)(3 + 2u) = 0 Multiply (1 + u) * (3 + 2u) (1(3 + 2u) + u(3 + 2u)) = 0 ((3 * 1 + 2u * 1) + u(3 + 2u)) = 0 ((3 + 2u) + u(3 + 2u)) = 0 (3 + 2u + (3 * u + 2u * u)) = 0 (3 + 2u + (3u + 2u2)) = 0 Combine like terms: 2u + 3u = 5u (3 + 5u + 2u2) = 0 Solving 3 + 5u + 2u2 = 0 Solving for variable 'u'. Factor a trinomial. (3 + 2u)(1 + u) = 0Subproblem 1
Set the factor '(3 + 2u)' equal to zero and attempt to solve: Simplifying 3 + 2u = 0 Solving 3 + 2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2u = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2u = 0 + -3 2u = 0 + -3 Combine like terms: 0 + -3 = -3 2u = -3 Divide each side by '2'. u = -1.5 Simplifying u = -1.5Subproblem 2
Set the factor '(1 + u)' equal to zero and attempt to solve: Simplifying 1 + u = 0 Solving 1 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + u = 0 + -1 Combine like terms: 1 + -1 = 0 0 + u = 0 + -1 u = 0 + -1 Combine like terms: 0 + -1 = -1 u = -1 Simplifying u = -1Solution
u = {-1.5, -1}
| f(x)=3x^4-4x^3 | | 60+21.50+21.50=124.50 | | n+124=436 | | 4x=10i | | log(9x+5)=4 | | -16t^2+72t-81=h | | j+j+(-14j)=-5 | | 6r^3-21r^2+9r=0 | | 3(3x+2)-7+2y=14 | | 12.5-7.5=7.5+12.5 | | 5-(1-2)= | | 3/4x^2=-1200 | | 1.3n-0.03=-9.00 | | 1.5X+4.5=0.8x-8 | | 5x-2(4x-12)=-7x-12 | | 41/82 | | 20-15=17 | | M/11=11 | | 32/x=2 | | 1/4(8x=20)=11 | | 2x^2-3x-8= | | 54=4x-10 | | 3+2=21 | | y-32=-4(x+5) | | x2=8/125 | | 7.056/5.88 | | x-0.05x=23.74 | | 1/3x-9=1/2x-6-5/6 | | 3.2+8.4x+9.33=6.2x-4.2 | | -44=4x-4 | | X-3/1/8=5/12 | | 4(x-2)=-3(x+4)-10 |